An analytical study of organizational confidence from the point of view of physical education teachers in al-rusafa 2 directorate - زينب علي كاظم العجيلي أ . م . د سندس موسى جواد (الرياضة المعاصرة)
The importance of the research lies in the fact that the educational institution relies heavily on the teachers in charge of educational and educational tasks in achieving its objectives as the focus of the educational and teaching process in it. The good performance of those in charge of administrative tasks is one of the most important basic requirements that the educational institution seeks at its various levels. The degree to which the school principal has confidence from the teacher of physical education in qualifying teachers and physical education and sports science teachers to carry out administrative tasks to provide decision-makers with information about them, so the objectives of the research were to build a measure of confidence of the school director in the physical education teacher, and the second semester the researchers used the descriptive approach in the two methods of survey and relationships Correlation, the two researchers identified the research community by the intentional method of physical education teachers working in the schools of the Rusafa Second Education Directorate, whose number is (393), either the research sample represented the entire research community, The data were statistically treated, so that the most important conclusions were to build a measure of confidence for the school principal in the teachers of physical education in the Rusafa Second Directorate of Education, and the most important recommendations were to use this scale in all educational and sports institutions, to conduct studies similar to the scale of (confidence in the school principal) and all their axes to benefit from this study .